Distribuição sazonal de parasitos branquiasis em diferentes especies de piexes em pesque-pague do municipio de Guariba-SP, Brasil. - Schalch, Sergio H C; Moraes, Flávio R de (My University, 2005)
This study was accomplished with the objective of knowing the seasonal distribution of the main species of parasites causes of branchial damages to the fish from fee-fishing at Guariba, State of São Paulo. This city is situated at 21 degrees 15'22'' S, 48 degrees 18'58'' W, in altitude 595 meters. This research was conducted between April, 1997 to March, 1999. From 408 fishes examined, 29.1% of them were infested by the protozoans e metazoans. Leporinus macrocephalus showed the highest parasitism by Trichodina sp., although Piaractus mesopotamicus and Cyprinus carpio were also parasited. Piscinoodinium pillulare infestation were found in L. macrocephalus, P. mesopotamicus, C. carpio e Colossoma macropomum. Monogenetics metazoan have largely been observed in L. macrocephalus, P. mesopotamicus, C. carpio, C. macropomum e cross-bred tambacu. The incidence of this parasite was elevated in the summer for L. macrocephalus, spring for P. mesopotamicus and C. macropomum, and both seasons for cross-bred tambacu. Lernaea cyprinacea copepodes were observed in L. macrocephalus, P. mesopotamicus, C. carpio and cross- breeding tambacu, in spite of the fact that C. carpio has demonstrated high parasitism of adult form. The fish L. macrocephalus, P. mesopotamicus and C. carpio were sponged intensely by Dolops carvalhoi, in situation of high population density. Piaractus mesopotamicus was considered the species more parasited by myxosporídeos, that were also observed in L. macrocephalus and cross-breeding tambacu.
Seasonal distribution of gill parasites in fishes from fee-fishing at Guariba, São Paulo State, Brazil
Keywords: animal; Brazil; fish; gill; isolation and purification; parasite; parasitology; season; Animals; Fishes; Gills; Parasites; Seasons